Solution‐Processed Transparent Superhydrophobic Protection Layers for Enhancing the Device Reliability of Flexible Organic Optoelectronics. Issue 8 (24th June 2020) - Yoo, Daekyoung; Kang, Keehoon; Kim, Youngrok; Ahn, Heebeom; Lee, Woocheol; Pak, Jinsu; Chung, Seungjun; Lee, Takhee
Abstract: Organic materials and devices have attracted great attention for implementation of flexible and transparent electronics applications. However, further easy‐to‐manage organic devices with acceptable environmental reliability in open air are desirable. Specifically, because water‐based threats and particle contamination can degrade the functions of organic optoelectronics, introducing a superhydrophobic protection layer onto organic devices, which can eliminate issues via excellent water repellency, is necessary. In this study, surface‐engineered TiO2 nanoparticles dispersed in a highly fluorinated solvent are deposited on organic devices using organo‐compatible solution processing. The optimization of the TiO2 nanoparticle layer, such as the surface roughness and thickness of the film, enables the realization of a transparent superhydrophobic layer; therefore, the film can be utilized in transparent organic optoelectronics, especially in phototransistor applications. The transparent superhydrophobic layer exhibits good water repellency without critical delamination issues even during mechanical deformation, such as bending and stretching tests. Flexible organic phototransistors with the transparent superhydrophobic layer show a self‐cleaning ability against harmful contaminants on the topmost surface, achieved by dropping water droplets. This work can provide a feasible solution to maintaining transparent and flexible organic devices with improved environmental reliability. Abstract : TiO2 nanoparticle‐based transparent superhydrophobic protection layers that can be directly deposited onto flexible organic phototransistors are reported. By controlling the surface roughness through a rinsing process, excellent film transparency can be achieved without degradation of the superhydrophobicity. The layers show good durability under light stress and mechanical deformation and enhance the reliability of organic phototransistors against water‐based threats and undesirable particle contamination.